Induksi Kalus Dan Inisiasi Tunas Bawang Merah (Allium Ascalonicum L.) Lokal Palu - Nulfitriani Nulfitriani; Zainuddin Basri; I Nengah Suwastika (Mitra Sains, 2017)
The aims of these experiments were to obtain appropriate concentrations of 2,4-D for callus induction and cytokinins for shoot initiation of shallot local palu. The concentrations of 2,4-D tested for callus induction namely 1 ppm, 2 ppm, 3 ppm, 4 ppm and 5 ppm; whilst concentrations of cytokinins tested for shoot initiation including 2 ppm, 3 ppm and 4 ppm for BAP or Kinetin. These experiments used Completely Randomized Design and each experimental unit utilized two explants with three replications. Data were computed and analysed by analysis of variance and tested with DMRT for identifying the differences between treatments tested. Results of these experiments indicated that callus induction as well as shoot initiation of shallot local palu were highly affected by concentrations of 2,4-D or cytokinins tested. The addition of 3 ppm 2,4-D into culture medium was the appropriate concentration for callus induction. At such medium composition, it was obtained the fastest callus formation (average 4.67 days after culture) and all explants cultured could produce calli. The addition of 2 ppm BAP into culture medium was the appripriate cencentration for shoot initiation of shallot local Palu. At such medium composition, it was obtained the fastest shoot formation (average 3.67 days after culture), the highest number of shoot formation (average 2.33 shoots per explant) and the highest chlorophyl content (53.6576) mg chlorophyl A per gram leaves.